Simultaneous measurement of intraluminal pressure and pH in the stomach and oesophagus: With special reference to the diagnosis of hiatal hernia and hiatal incompetence. Issue 5 (September 1969) - Lockwood, Knud; Borgeskov, Sven
Abstract : A short survey is given of the theoretical background for the simultaneous measurement of intraluminal pressure and p H in the oesophagus and stomach as well as the method used in the paper presented. In 20 of 23 patients with symptoms of regurgitation this was sustained by the p H measurement (87%). In only 20% was incompetence demonstrated radiologically. The p H measurement is of especial value in the diagnosis of oesophageal reflux. The value of simultaneous pressure measurements is to ascertain the position of the electrode distally or proximally to the oesophageal hiatus. Thus we suggest that pressure and p H measurements are mandatory in future post-operative follow-up examinations in patients operated upon for hiatal herniae.